Balanço de radiação e evapotranspiração na bacia hidrográfica do Rio Jacaré - SE mediante imagens orbitais - Batista, Wagner Roberto Milet (2011)
This study aimed to estimate the radiation balance terms and the daily evapotranspiration (ET) through (TM) - Landsat 5 images and supplemental data available at a meteorological station located in the study area. The study area occupies part of the municipalities: Poço Redondo city and Canindé do São Francisco city in Sergipe State, as part of the lower São Francisco. Setting up a tributary of the right bank of the São Francisco River. The Jacare River basin rises near the border of Bahia/Sergipe state in Bonito mountain and has a length of 73.5 km Hydrological basin area is 943.9 km2, the perimeter of the area is 142.7 km. Therefore, we used two images obtained from the National Institute for Space Research (INPE) for the day October 17, 1999(day 290) and December 6 (day 341), 2006. The net radiation (Rn) and sensible heat (H) and soil heat (G) and latent heat (LE) fluxes were determined by the algorithm Surface Energy Balance Algorithm for Land (SEBAL). Examined the observed results that showed an average snapshot (Rn) de 585,1 e 578,7 W/m2 for days 290 and 341 respectively. The density of soil heat flux (G) which was obtained as a function of Rn, surface temperature, albedo, normalized difference vegetation index (NDVI), and parameterization proposed by Bastiaanssen (2000) showed an average of 92.4 and 111.8 W/m2 on days 290 and 341, respectively. The flux density of sensible heat (H) showed an average of 230.5 and 295.6 Wm2 in 290 and 341, respectively. The density of latent heat flux (LE), calculated as the residual energy balance equation showed an average of 260.3 and 169.3 W/m2 on days 290 and 341, respectively. The ET daily showed average values of 2.6 and 1.7 mm.day-1 for days 290 and 341, respectively.